Correlation between Sever Anemia and Pregnancy Complications - Ayesha Iqbal; Sana Afridi; Saman Zafar; Nazia Wahid; Munazza Yousaf (Indus Journal of Bioscience Research, 2025)
This prospective observational study aimed to assess the impact of anemia severity on maternal and perinatal outcomes in 200 pregnant women. The participants were categorized into three groups based on their hemoglobin levels: mild anemia (10.0–10.9 g/dL), moderate anemia (7.0–9.9 g/dL), and severe anemia (